THE HUMOR IN IRONY THROUGH THE CHARACTERS OF LLYOD AND HARRY IN “DUMB AND DUMBER” MOVIE - Arif, Citra Ainun; Nurfadhilah, Auliyanti Sahril (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
In this research study, the researcher aims to find out the use of humor in irony by the characters Llyod and Harry in the movie “Dumb and Dumber”. The main source of data for this research is the movie Dumb and Dumber (1994). Dumb and Dumber (1994) was written by Peter Farrelly, Bennet Yellin, Bobby Farrelly, and directed by Peter Farrelly. It was released by New Cinema and produced in the United States by Brad Krevoy. In this study, we examined the type of irony in the movie “Dumb and Dumber” and humor in irony through the characters of Llyod and Harry in the movie “Dumb and Dumber”. In examining the type of irony, we used Abram’s theory (1999) and for humor we used Raskin’s theory (1984). Descriptive qualitative method was used in this research, in which we watched the film, observed, analyzed the data and complied then drew conclusions. We found that the characters in the movie “Dumb and Dumber” used all types of irony in 23 extracts. Verbal irony, situational irony and dramatic irony can be found in this movie. For humor in irony that appears through the characters of Llyod and Harry in this movie, it is found in various ways of expression so as to bring humor in it.